Improving Students’ Listening Skill Using Tangled Animation Movie - Nurjanah, Ebta; Jajat Imanudin; Fovi Sriyuliawati (Universitas Islam Al-Ihya Kuningan, 2024)
The objective of the study was to analyze and describe the process of improving students’ listening skill for eight grade students of SMP Negeri 3 Kuningan, West Java Province Using Tangled Animation movies. The subject of this research is VIII C class that consisted of 30 students. The method used in this study is Classroom Action Research (CAR) which the writers work collaboratively with the English teacher. This study was conducted following Kemmis and McTaggart action research procedures: planning, acting, observing, and reflecting. The study carried out in two cycles. The results in this study indicate that there was improvement of the students’ skill listening. Most of the students gradually gained good scores at the end of the cycle. The score of Minimum Mastery Criterion (KKM) of English lesson was 70.00. In the pre-test, there were 5 or 16% students who passed the KKM and the mean score of pretests was 56,66. The result of post-test 1 in cycle one, there were 14 students or 47% who passed the KKM considering their mean score of the test gained 65,83. Next, the result of post-test 2 in the second cycle shows that there were 24 students or 76,16%who passed the KKM and gained 34% of improvement. The class condition during teaching learning process was good also there was a positive response from the English teacher and the students towards the action. In conclusion, using Tangled Animation Movie can improve students’ listening skill.